Physical growth of school children at both sea level and moderate altitude - Cossio-Bolaños, Marco Antonio (2012)
hypoxia as well as to socioeconomic, nutritional and environmental factors. Objectives: To compare physical growth of school children in Peruvian urban areas at sea level (150 meters above sea level) and moderate altitude (2 320 m.a.s.l.). Design: Ex post facto design, descriptive comparative study. Institution: Faculty of Physical Education, State University of Campinas, SP, Brazil, and Universidad Nacional de Educacion, Lima, Peru. Participants: School children. Interventions: A total of 1 153 boys and girls aged 6 to 11 years were selected from two Peruvian geographical regions, one at sea level (SL) (Lima-East; 150 m.a.s.l.) and the other at moderate altitude (MA) (urban Southern Arequipa; 2 320 m.a.s.l.). School children at SL were chosen in non-probabilistic intentional way, totaling a subsample of 672 children. Pupils at moderate altitude (MA) were selected by stratified probability, resulting in 792 children from a total of 5 627 school children. Decimal osmolality and body mass and height, variables of physical growth, were assessed. Results were analyzed using arithmetic mean (X), standard deviation (SD) and percentile distribution. ‘T’ student test was used to compare groups, and independent samples (p <0.001) and distributions (p5, p10, p25, p50, p75, p85, p90 and p95) were compared according to the fraction 100 log (percentile of the reference/percentile calculated). Main outcome measures: Body mass and height growth. Results: Children of both genders and all ages at sea level had higher body mass in relation to children at moderate altitude. However, height did not differ significantly, with similar growth behavior at ages 6 to 11. Conclusions: These findings suggest that moderate altitude hypoxic stress does not affect stature growth in Arequipa’s (2 320 m.a.s.l.) school children. Children at sea level had a tendency to overweight and obesity.